Evaluating peer-based youth programs: barriers and enablers - Lobo, Roanna; McManus, Alexandra; Brown, Graham; Hildebrand, Janina; Maycock, Bruce (Australasian Evaluation Society, 2010)
Peer-based programs are increasingly used by community organisations to support vulnerable youth who are at risk of developing mental health problems. Such programs are as diverse as the populations they support and include drop-in services, peer education, camps and online discussion forums for hard-to-reach populations that may not access more conventional forms of support owing to issues of stigma or accessibility (for example, same-sex-attracted youth and teenage parents). There has been limited evaluation of peer-based community programs. Therefore, the lack of evidence of program effectiveness makes it difficult for service providers to secure continuous funding and threatens program sustainability. This article reports on a study designed to investigate barriers and enablers associatedwith evaluating peer-based youth programs. The resulting implications for policy, practice and research are discussed.